The role of white wing bands in parental care and mate choice in the female Common eider (Somateria mollissima) - Hoholm, Marte Sørbø (Universitetet i Tromsø, 2008)
The female Common eider (Somateria mollossima) is a drab, lightly coloured bird, easily distinguished from the brightly ornamented male. Unlike the male, the female has white bands on the tips of her wings, and these white wing bands have been shown to reflect individual quality in previous studies. In this study the potential role of the white wing bands in parental care and mate choice is studied, predicting that females without wing bands should tend for their brood less often, and get less interest from males, when compared to females with normal wing bands. The size of the wing bands was manipulated in two different studies, to explore if it influenced the females’ brood tending behaviour and the interest from males respectively, during breeding season. The study of brood tending behaviour did not indicate a clear connection between experimental manipulation of the wing band size and brood tending behaviour. However, the natural variation in wing band size did relate to parental care, where females with larger natural wing bands tended for their brood more often than females with smaller wing bands. The study of male interest showed that males preferred females in the control group, with visible white wing bands, more often than females with removed wing bands. These results indicate that the white wing bands of the female Common eider play a role in both parental care and male mate choice.